Hubungan Beban Kerja dan Motivasi Kerja Karyawan Hotel - Ketut Ratna Dewi; Ni Putu Dian Utami Dewi; Sutrisna, I Putu Edi (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2024)
The phenomenon of increasing workload felt by employees at The Patra Bali Resort & Villas raises a problem where employee motivation is still high. This phenomenon is certainly not in line with the opinion of Haryono, et al (2009) which states that excessive workload can trigger a decrease in morale and work motivation. Which means that if the workload given is high it will cause a decrease in employee motivation. However, it is different from the theory of goal setting theory according to Lucke & Latham (1990) this theory states that a difficult goal or a goal that has a high degree of difficulty can increase one's work motivation.  This study examines the correlatino workload between employee motivation at The Patra Bali Resort & Villas hotel. This study aims to analyze the level of workload at The Patra Bali Resort & Villas hotel, to analyze the level of employee motivation at The Patra Bali Resort & Villas hotel, and to analyze how workload relates to employee motivation at The Patra Bali Resort & Villas hotel. Villas. This research method is a quantitative method with a correlational associative approach. The population in this study were all hotel employees. The number of samples in this study amounted to 103 respondents to the determination of the sample using simple random sampling. Furthermore, the instruments use in this study were questionnaires and interview guides. The instrument use has gone through validity and reliability tests. To answer the problem formulation using descriptive statistical tests and Pearson product moment correlation analysis. Based on the results of the  descriptive statistical test regarding the level of workload it was found that the  workload at The Patra Bali Resort & Villas hotel was in the High category with the  mean result being 39.49, from the results of the descriptive statistical test it was  found that the level of employee motivation at The Patra Bali Resort hotel & Villas  is in the very high category with a mean result of 41.04 and the Pearson product  moment correlation analysis shows that workload and work motivation have a weak  relationship with an r value of 0.206 and a significant level of data confidence.